Combinations of plant essential oils and their major compositions inducing mortality and morphological abnormality of Aedes aegypti and Aedes albopictus - Mayura Soonwera; Tanapoom Moungthipmalai; Jirapon Aungtikun; Sirawut Sittichok (Heliyon, 2022)
EO + trans-anethole, are natural compounds that not only are as effective as temephos at the time of this study, but should be also be much safer to human health.
Keywords: Insect Pest Control Strategies; Moringa oleifera research and applications; Insect Utilization and Effects